Sustainability communications via sponsorship: Potential, characteristics and managerial challenges - Stefan Walzel; Christopher Dick; Maximilian Brill; Gerhard Nowak (Sustainable Development, 2024)
Sustainability communications have become a key issue for organisations. While most studies have focused on sustainability reporting and green advertising, other communication tools such as sponsorship are under-researched. The present study addresses this void by exploring the potential and identifying key characteristics and challenges of sustainable sponsorships, theoretically conceptualised as a social contract between sponsorship contractors and society. As such, it is the first to identify the potential and key characteristics of sponsorship for sustainability communications. The authors took an explorative, qualitative research approach, conducting 13 in-depth interviews. The interviewees highlighted eight characteristics that determined sustainable sponsorships across all three sustainability dimensions. Sustainability was identified as a key driver in managing sponsorship effectively. In light of the study's findings, it is recommended that sponsors and sponsees should adapt their sponsorship management to incorporate sustainability. Measuring the outcome and success of sustainable sponsorships could be a subject for future research.
Keywords: 330; communication; CSR; development goals; legitimacy; sponsorship; sustainability